Safety assessment of disulfiram: real-world adverse event analysis based on FAERS database - Luo, Jing; Zeng, Yaqi; Chen, Zhe; Luo, Yaan; Shi, Li; Zhou, Xuhui (Frontiers in Psychiatry, 2024)
ObjectiveDisulfiram, an FDA-approved medication for AUD, has shown significant potential as a repurposed drug in therapeutic areas including oncology and infectious diseases. The purpose of study is to analyze adverse events (AEs) associated with disulfiram by examining the FAERS database, with a focus on understanding its safety profile in both traditional and emerging applications.MethodsAE reports concerning disulfiram in the FAERS database from the fourth quarter of 2002 to the third quarter of 2023 were extracted. Various signal detection methods, including ROR, PRR, BCPNN, and MGPS, were used to detect and categorize adverse events.ResultsThe study collected 52,159,321 AE reports, with 508 reports primarily suspecting disulfiram, identifying 104 Preferred Terms (PTs) across 25 System Organ Classes (SOCs). Major categories of AEs included off label use, psychiatric symptom, liver transplant, and polyneuropathy, with off label use being notably the most reported issue. Strong and new potential AEs were identified, including neurological and psychiatric issues like hypomania, delirium, and vocal cord paralysis; cardiac issues such as electrocardiogram st segment depression; and off label use-related issues like Jarisch-Herxheimer reaction.ConclusionDisulfiram poses risks of various adverse reactions while having promise as a “repurposed” agent. In clinical applications, practitioners should closely monitor occurrences of hepatobiliary disorders, psychiatric disorders, and nervous system disorders.